2008
DOI: 10.3748/wjg.14.511
|View full text |Cite
|
Sign up to set email alerts
|

Chaga mushroom (Inonotus obliquus ) induces G0/G1 arrest and apoptosis in human hepatoma HepG2 cells

Abstract: Chaga mushroom may provide a new therapeutic option, as a potential anticancer agent, in the treatment of hepatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 28 publications
9
46
0
3
Order By: Relevance
“…Thus, most of bioactive substances from natural products have been reported to exert their anticancer activity by blocking cell cycle progression and triggering tumor cell apoptosis (Chang et al, 2004;Ye et al, 2005;Hsieh et al, 2006). Youn et al (2008) confirmed that I. obliquus water extract (IWE) previously used for treating cancers and digestive system diseases could selectively and significantly inhibited the viability and proliferation, and induced apoptotic cell death in human hepatoma HepG2 cells, while this effect was not found in the human immortalized non-tumor cell line. HepG2 cells were dose-dependently arrested by IWE at the G0 /G1 phase of the cell cycle, and cyclin D1 and Cdk2, and Cdk6, which were responsible for most of the cell cycle arrest, were effectively deceased at the lowest dose of IWE.…”
Section: Involving In the Arrest Of Cell Cycle In Cancer Cellsmentioning
confidence: 74%
“…Thus, most of bioactive substances from natural products have been reported to exert their anticancer activity by blocking cell cycle progression and triggering tumor cell apoptosis (Chang et al, 2004;Ye et al, 2005;Hsieh et al, 2006). Youn et al (2008) confirmed that I. obliquus water extract (IWE) previously used for treating cancers and digestive system diseases could selectively and significantly inhibited the viability and proliferation, and induced apoptotic cell death in human hepatoma HepG2 cells, while this effect was not found in the human immortalized non-tumor cell line. HepG2 cells were dose-dependently arrested by IWE at the G0 /G1 phase of the cell cycle, and cyclin D1 and Cdk2, and Cdk6, which were responsible for most of the cell cycle arrest, were effectively deceased at the lowest dose of IWE.…”
Section: Involving In the Arrest Of Cell Cycle In Cancer Cellsmentioning
confidence: 74%
“…Youn et al advocated I. obliquus extract inhibited the growth of HepG2 cells in a dose-dependent manner, which was accompanied with G 0 /G 1 phase arrest and apoptotic cell death. In addition, G 0 /G 1 arrest in the cell cycle was closely associated with down-regulation of expression (Youn et al, 2008). Then, Youn et al further demonstrated I. obliquus extract inhibited the growth of B16-F10 cells by causing cell cycle arrest at G 0 /G 1 phase and apoptosis (Youn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Более поздние исследования показали, что применение водного экстракта чаги уменьшает размер опухолей саркомы МОП и S180, карциномы лёгких Льюиса и карциномы Эрлиха, меланомы B16-F10, глиобластомы U-87 MG [33,34,[53][54][55][56], а также оказывает антиметастатическое действие in vivо: на клетки саркомы, аденокарциномы шейки матки HeLa, карциномы Эрлиха, и in vitro на клетки гепатомы, рака толстой кишки, саркомы 180 [15,30,41,53].…”
Section: Introductionunclassified
“…Например, А, А2, А7, А15 оказали in vitro выраженный гепатопротекторный эффект: 74,8, 81,2, 75,0 и 71,9% соответственно по отношению к контролю -гепатопротектору бициклолу [26]. А1 и А5 проявляют гипогликемические свойства in vitro [55,59], А2, А5 и А24 -противогрибковые свойства in vitro, A1, А2,A5, Б, Б3 -противовоспалительные свойства in vitro [35], А1, А5, А23 -антиоксидантные свойства [36]. А1 и А5 обладают антимутагенным действием, снижают уровень мутагенов MNNG, 4NQO, в Salmonella typhimurium TA98 и TA100 [63].…”
Section: Introductionunclassified